2013
DOI: 10.7717/peerj.82
|View full text |Cite
|
Sign up to set email alerts
|

What is the “normal” fetal heart rate?

Abstract: Aim. There is no consensus about the normal fetal heart rate. Current international guidelines recommend for the normal fetal heart rate (FHR) baseline different ranges of 110 to 150 beats per minute (bpm) or 110 to 160 bpm. We started with a precise definition of “normality” and performed a retrospective computerized analysis of electronically recorded FHR tracings.Methods. We analyzed all recorded cardiotocography tracings of singleton pregnancies in three German medical centers from 2000 to 2007 and identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(61 citation statements)
references
References 21 publications
1
59
1
Order By: Relevance
“…Indeed, a large cohort study by Pildner von Steinburg et al 109 showed the incidence of bradycardia and tachycardia at rest (exercise was not examined) to be 0.12% and 3.71%, respectively, whereas we reported a 95% CI of 0% to 3% for bradycardia and 0% to 14% for tachycardia. Future studies looking at FHR longitudinally (ie, comparing incidence of bradycardia and tachycardia at rest, during and following exercise) are required.…”
Section: Discussioncontrasting
confidence: 67%
“…Indeed, a large cohort study by Pildner von Steinburg et al 109 showed the incidence of bradycardia and tachycardia at rest (exercise was not examined) to be 0.12% and 3.71%, respectively, whereas we reported a 95% CI of 0% to 3% for bradycardia and 0% to 14% for tachycardia. Future studies looking at FHR longitudinally (ie, comparing incidence of bradycardia and tachycardia at rest, during and following exercise) are required.…”
Section: Discussioncontrasting
confidence: 67%
“…Biphasic stimulation compared to monophasic stimulation decreases the excitation threshold and increases cell viability [107]. When hPSC-CMs resemble immature fetal CMs, electric stimulation at 1Hz is non-physiologic since the fetal heart has a beating rate between 2 and 3Hz [110]. In a recent study, stimulation at 6 Hz promoted cellular and functional maturation of hPSC-CMs [108].…”
Section: Bioelectrical Features Of the Cardiac Nichementioning
confidence: 99%
“…A counter weight prevents the heart phantom from floating away and guarantees a stable sinusoidal motion pattern. The adjustable driving voltage of the motor is set such that it simulates the normal average fetal heart rate of 140 beats per minute [7]. The distance between the rotary hinge and the motor was tuned, such that the distance covered by the phantom during one cycle is equal to the distance covered by the fetal cardiac wall during one heart beat, i.e.…”
Section: B Fetal Beating-heart In-vitro Setupmentioning
confidence: 99%